Creating fatigue curve for steel machine elements using fatigue test method with gradually increasing stress amplitude - Dung, Nguyen Dinh; Huy, Vu Le; Bao, Hoang Van (Vietnam Journal of Science and Technology, 2020)
In order to create a fatigue curve, the traditional fatigue test method is applied to specimens using a cyclic stress with constant amplitude. However, this method has disadvantages such as the experimental results could not be used because of specimens broken before reaching the expected stress amplitude, or the tests may be stopped before specimen broken because of limitation of time. To overcome this hurdle of the traditional method, a new experimental method using cyclic stress with gradually increasing amplitude was proposed to build the fatigue curve for steel machine elements.